Relationship Between MCH Handbook Utilization and Pregnant Women's Knowledge of Daily Care at Tanah Kalikedinding Health Center - pravitasari, Gading Indah; Ratna Dwi Jayanti; Budi Utomo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Indonesia is one of the countries with the highest maternal mortality rates (MMR) in Southeast Asia with a rate of 189 per 100,000 live births based on the 2020 Long-Form Population Census. This figure needs to be significantly reduced to achieve the 2030 Sustainable Development Goals (SDGs) target of fewer than 70 deaths per 100,000 live births. Proper antenatal care, including the use of the Maternal and Child Health (MCH) Handbook, plays a crucial role in reducing maternal mortality. Pregnancy care is vital to ensure fetal development, prevent pregnancy complications, and lower the risk of infant mortality during childbirth. Objectives: This study aims to conduct a scientific investigation to examine the relationship in the utilization of the MCH handbook with the level of maternal knowledge among pregnant women at the Tanah Kalikedinding Health Center. Methods: This observational analytic study used a cross-sectional design. The selection of 106 participants was carried out using purposive sampling. Data were analyzed using the Spearman rho statistical test. Results: Among the respondents, 51 (48.11%) demonstrated adequate utilization of the MCH Handbook and 89 (83.96%) exhibited a high level of knowledge regarding daily care for pregnant women. The Spearman rho test revealed a significant relationship between MCH Handbook utilization and knowledge of daily care (p = 0.042). Conclusion: There is a significant relationship between the use of the MCH Handbook and pregnant women’s knowledge of daily care at Tanah Kalikedinding Health Center.